SISTEM DIAGNOSA PENYAKIT CORONA DENGAN METODE CASE-BASED REASONING DAN CERTAINTY FACTOR - Hendrawaty Hendrawaty; Alfiya Zahara; Azhar Azhar (Jurnal Real Riset, 2022)
Expert systems are part of a general category of computers known as intelligence.Created an expert system to work on a particular domain. In artificialintelligence, an expertsystem is a computersystemthat imitates the decision-making abilities of humans who are experts in theirfields. The main thrust of artificial intelligence is in developing, solving problems,to build a knowledge-based system in the specific medical field in the domain toaim at diagnosing Covid-19 through the application of an expert system in theform of symptom input. This has prompted the creation of an expert system for diagnosing Covid 19 using the Case Base Reasoning and Certainty Factormethods based on the Responsive Web. The Certanty Factor method is used tofind the certainty value of the disease by calculating the probability value of thedisease symptoms and Case Based Reasoning to find the similarity value of thedisease with the previous case. Based on the calculation results, the expert systemcan be used for early diagnosis of the disease. The result of this study is that thesystem can assist experts in diagnosing Covid-19 disease based on the results ofsystem testing through surveys by conducting interviews with Covid-19 experts.This study also tested the software using the Black Box method.Keywords : casebased reasoning, certainty factor, covid-19,expert system